Interpretation of production tests in geothermal wells with T2Well-EWASG. (May 2018) - Vasini, Ester Maria; Battistelli, Alfredo; Berry, Paolo; Bonduà, Stefano; Bortolotti, Villiam; Cormio, Carlo; Pan, Lehua
Highlights: T2Well-EWASG, a coupled wellbore-reservoir numerical simulator for geothermal systems. Interpretation of geothermal well-tests. Application of T2Well-EWASG on a short well-test performed on a well of the Wotten Waven geothermal field (Dominica). Abstract: In the geothermal sector, being able to simulate production tests by combining surface and downhole measurements can be extremely useful, improving data interpretation and reducing the impact of unavailable field data. This is possible with T2Well, a coupled wellbore-reservoir simulator. We plugged the EWASG equation of state for high enthalpy geothermal reservoirs into T2Well and extended the function to analytically compute the heat exchange between wellbore and formation at the short times. Changes to the analytical heat exchange function were verified by comparison with wellbore-formation heat exchange numerically simulated. T2Well-EWASG was validated by reproducing the flowing pressure and temperature logs taken from literature, and by using the software for the interpretation of a short production test. Simulation results indicate that T2Well-EWASG can be effectively used to improve the interpretation of production tests performed in geothermal wells.